(untitled) (Research, Society and Development, 2022)
The present research aimed to analyze the legal treatment given to indigenous populations in the border region between Brazil and French Guiana, especially with regard to the non-recognition of indigenous peoples by France due to constitutional limitations and, by Consequently, the non-ratification by that country of Convention 169 of the International Labor Organization – ILO. The methodology used was the deductive method; as for the means of research, it was bibliographic, using doctrine, articles, books, legislation and jurisprudence; and as for the purposes, it was a qualitative research. It was possible to conclude that the lack of adequate guarantee of the rights of indigenous peoples by France causes damage to the preservation of the culture and language of these peoples, with the potential to affect the indigenous populations on the Brazilian side of the border. This proves to be a hindrance to the adoption of specific public policies aimed at these populations by the French State.